PERILAKU KOMUNIKASI VERBAL PENYIAR RADIO DI KOTA PEKANBARU - Mia Lestari; Genny Gustina Sari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
In a broadcast media the rise and fall of existence is normal. Along with the increasing competition in the broadcasting world, all broadcast media are working hard to maintain their existence. One form of broadcast media is radio. The announcer is the spearhead of the radio, representing the radio. He interacts directly with listeners. Therefore radio announcer are required to have good verbal communication behavior in order to maintain the existence of the radio itself. This study aims to determine aspects of verbal communication behavior carried out by broadcasters as well as obstacles in verbal communication of radio broadcasters in Pekanbaru.               This study used qualitative research methods. The research subjects were determined based on purposive sampling technique consisting of 5 radio broadcasters selected based on radio recommendations and 2 radio listener. This research was conducted at Persada 93.2 FM, Gress 15.8 FM and Warna 104.2 FM Pekanbaru. Data collection techniques include observation, interviews, and documentation               The results of this study indicate that verbal communication behavior with radio broadcasters includes 1. Vocabulary using Indonesian, some slang (informal) which will make communication more effective. 2. Racing (speed) communication will affect the reception of messages, 3. Intonation (emphasis) voice made by broadcasters adjusted to the theme of the program delivered so that there is no misunderstanding in sending messages if the message is delivered with intonation that is not appropriate. 4. Humor is used as a distraction when the announcer communicates with the listener but is considered to place humor so that communication is not rigid and attractive. 5. Short and clear language, which is sending messages made by radio broadcasters to listeners must use short and clear language so that listeners are not bored and are interested in listening to what radio broadcasters say. 6. Timing settings (time) is to choose the right time when delivering messages to listeners. 7. Internal and External Barriers are Health Barriers, Anthropological Obstacles, Psychological Obstacles, Ecological Barriers and Mechanical Barriers. Keyword: Self Representation, Indentity Virtual, Cyber Community